Derrida, the Gift and John Barclay's Paul and the Gift - McFarlane, Graham W. P. (The Evangelical quarterly, 2018)
Simon Wiesenthal encapsulates the impossibility of forgiveness in the face of Holocaust evil. Deconstructionist, Jacques Derrida articulates what he describes as the aporia of forgiveness-that once given it degenerates into an economy of exchange and thus negates the 'purity' of forgiveness. In Paul and the Gift John Barclay offers a New Testament response to contemporary voices. He argues that whilst the gift of the gospel is unconditional, it does not come unconditioned and identifies she 'perfections' of the gift of grace we receive in response to the Gospel. The free gift does indeed come with conditions. Anselm and McLeod Campbell are offered as examples of atonement that incorporate various aspects of Barclay's presentation of gift.